PENGARUH LABA BERSIH DAN ARUS KAS TERHADAP DIVIDEN PERUSAHAAN SEKTOR INDUSTRI BARANG DAN KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2018-2021 - Raisya Puspa Septiani; Tellyta Maulani (Institut Bisnis Muhammadiyah Bekasi, 2023)
Profits and cash receipts are the most important issues management must consider and compare when making stock or cash payment decisions. Because the form of influence is positive, the greater the net profit obtained, the greater the dividend that will be distributed to investors. This research was conducted with the aim of clarifying profits and cash receipts by paying in shares or cash based on the commodity and consumer sectors listed on the Indonesian stock exchange for the 2018-2021 period. This study uses an associative approach with quantitative data types, where the data source used is data that is indirectly from the object. The population involved is commodity and consumer sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period. This sampling procedure is a non-probabilistic sampling. The data analysis technique used is descriptive analysis, classical hypothesis testing, multiple regression analysis, and hypothesis testing. The results of this study indicate that while net income may not have a significant effect on cash dividends, operational cash flow has a significant impact on cash dividends. But at the same time, net profit and operating cash flow have a significant impact on cash dividends.